PEMANFAATAN SOSIAL MEDIA CAGAR BUDAYA SEJARAH JATIM DALAM PELESTARIAN CAGAR BUDAYA DI KOTA SURABAYA - Octama Dwirista; Mudammad Fadeli; Tira Fitriawardhani (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2022)
Cultural Conservation is material cultural heritage in the form of Cultural Conservation Objects, Cultural Conservation Buildings, Cultural Conservation Structures, Cultural Conservation Sites, and Cultural Conservation Areas on land and/or in water that need to be preserved because they have important values for history, science, education. , religion, and/or culture through the determination process. This study aims to determine the use of the Instagram account @cagarkultur_sejarahjatim in preserving cultural heritage in the city of Surabaya. This research use desciptive qualitative approach. The results of the study show that the observations that occur in the video publication of cultural heritage in the city of Surabaya which are presented through the posting of the Instagram account @cagarkultur_sejarahjatim in their publications use many choices of persuasive sentences in concise and simple language so that they are easy to understand. Some of the connotative meanings in the video of cultural heritage in the city of Surabaya show culture that must be preserved and maintained as well as possible so that it can be used as a cultural heritage in Indonesia.